A feasibility study on the establishment of a local church library for the first free Methodist Church of Manila - Guimary, Jo-ann T.; Timoteo, Christine B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Church libraries have been in existence for centuries already but where in the past access had been limited to the clergy, now all members of any the congregation have access to the same materials. The objective of this paper was to determine whether it is feasible to establish a library in the First Free Methodist Church of Manila. Feasibility was determine in three areas: market, technical and organizational, and financial.
The methodology followed by the study included different research instruments to be able to gather data for the three major areas in conducting a feasibility study. In determining the market feasibility, a questionnaire was employed.
The questionnaire had two versions, one for the adults and another for the children. A total of forty-six(46) adults and (9)children participated in the market study. Data gathered from the questionnaire were tabulated and computed. In the technical and organizational aspect of the study, the Christian Education Director, Lucette Miranda, and the Senior Pastor, Reverend Diana Aquino, were interviewed. Their responses were noted, summarized, and included in chapter iv. In the financial aspect of the study, the Church Treasurer/Finance Committee Head, Thelma Lizada, and, the Senior Pastor,Rev.Diana Aquino, were interviewed. The interviewees' responses were noted, summarized, and included in the presentation of data.
The market study revealed that the respondents of the study, nine(9) children and forty-six (46) adult members of the congregation of the church, mostly made of students and professionals, showed a 100 interest and willingness to support the establishment of a local church library.
The findings also showed that the respondents indicated a need to access reading materials that duel on topics related to their religious and spiritual lives. Interviews with the Christian Education Program Head and the Senior Pastor of the church revealed that the technical and organizational requisites such as library room, furnishings and equipment, other library supplies, organizational structure, and other factors recommended for church libraries by Betty McMichael (1987) were practicable and adaptable to the local church setting. Financial feasibility discussed with the Church Treasurer/Finance Committee Head and Senior Pastor revealed the possibility of a monthly allocation from the General Church Budget. Fund raising activities mentioned in the interview were evaluated as possible and permissible to be able to fund the operation of the church library.
Recommendations include a revised and adapted organizational structure for the subsequent church library, a fee schedule, a collection development policy statement, a list of qualification for the members of the library committee, librarian, and library staff, among others.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Church libraries -- Philippines -- Manila; Methodist church -- Philippines -- Manila